2010
DOI: 10.1212/wnl.0b013e3181feb2bf
|View full text |Cite
|
Sign up to set email alerts
|

The 32-year relationship between cholesterol and dementia from midlife to late life

Abstract: These data suggest that midlife cholesterol level is not associated with an increased risk of AD. However, there may be a slight risk among those surviving to an age at risk for dementia. Declining cholesterol levels from midlife to late life may better predict AD risk than levels obtained at one timepoint prior to dementia onset. Analytic strategies examining this and other risk factors across the lifespan may affect interpretation of results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 28 publications
(43 reference statements)
4
119
2
Order By: Relevance
“…The association between plasma lipoprotein profiles and risk of development of clinical manifestations of dementia has been controversial. An association between high cholesterol levels in midlife and an increased risk for dementia in old age has been suggested by several publications [68], but it was not confirmed by a recent large population study [69]. Instead, this study found that low cholesterol levels in late life were predictive of subsequent dementia.…”
Section: Alzheimer Diseasecontrasting
confidence: 81%
“…The association between plasma lipoprotein profiles and risk of development of clinical manifestations of dementia has been controversial. An association between high cholesterol levels in midlife and an increased risk for dementia in old age has been suggested by several publications [68], but it was not confirmed by a recent large population study [69]. Instead, this study found that low cholesterol levels in late life were predictive of subsequent dementia.…”
Section: Alzheimer Diseasecontrasting
confidence: 81%
“…The older age of the current sample may again partially explain these findings because the presence of these factors during midlife appears to represent the critical risk window for developing AD, and this risk is attenuated or reversed in late-life possibly due to survival bias (21,(53)(54)(55)(56)(57)(58)(59)(60) and the increased prevalence of these conditions with aging. When examined as a continuous variable, PP has previously been found to be unrelated to the clinical diagnosis of AD in a sample of !75 year olds, and other studies have also failed to find an association between antemortem PP and ADNP severity (10,20).…”
Section: Discussionmentioning
confidence: 85%
“…Many case -control studies have also confirmed that mild hypercholesterolemia accompanies late-onset AD [49,62,63]. However, a 32-year long follow-up study of 1462 women has failed to find an association of mid-life hypercholesterolemia with increasing risk of AD, and even some studies have indicated that a high blood cholesterol especially in latelife is actually protective against AD [64,65,66]. The statin group of cholesterol lowering agents has been shown to produce beneficial effects in AD subjects in some studies [67].…”
Section: Metabolic Risk Factors Of Ad: Present Statusmentioning
confidence: 99%